Parasocial interaction and problematic use of short-form video applications: unveiling the mediating mechanism - Qing Huang; Qing Huang; Sihan Lei; Sihan Lei; Zhuo Chen (Frontiers in Psychology, 2025)
IntroductionProblematic use of short-form video applications (SVA) has posed significant challenges to individuals' wellbeing in recent years. This study examines how parasocial interaction-a one-sided and imagined emotional engagement with vloggers—contributes to problematic SVA use.MethodsBased on the socio-psychological perspective and informed by the positive reinforcement and compensatory use approaches, the research explores how flow experience and fear of missing out mediate this association. An online survey was conducted among SVA users (N = 407). The collected dataset was analyzed using SPSS PROCESS Macro model 6 to test a serial mediation model.ResultsResults support the mediation model, indicating that the reinforcement of positive feelings and the compensatory motivation for alleviating negative emotions jointly lead to the problematic behaviors.DiscussionThe findings offer valuable insights into the socio-psychological processes underlying problematic SVA use and suggest potential intervention strategies to promote healthy usage of SVA.